2004
DOI: 10.1097/00000542-200404000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Anesthesia and Recovery from Radical Prostatectomy

Abstract: The benefits of improved immediate analgesia and decreased morphine requirements resulting from intrathecal analgesia must be weighed against factors such as pruritus, increased intraoperative requirement for fluids and vasopressors, and resources needed to implement this modality. Further studies are needed to determine the significance of the decrease in duration of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 12 publications
2
66
1
1
Order By: Relevance
“…Brown et al 16 reported that one patient who presented bradycardia was withdrawn from the study to investigate myocardial infarction, which was not confirmed at the end of the study. The data from Shir et al 19 and…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Brown et al 16 reported that one patient who presented bradycardia was withdrawn from the study to investigate myocardial infarction, which was not confirmed at the end of the study. The data from Shir et al 19 and…”
Section: Discussionmentioning
confidence: 94%
“…[11][12][13][14][15][16][17][18][19][20][21] Pooling the results to produce a meta-analysis was not possible. The decision not to perform a meta-analysis took into account the fact that the interventions and outcomes assessed were different among the RCTs included.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations